Experimental Evaluation of Bio-Based Materials in Epoxidation Techniques - Syed Zulqarnain Shah; Muhammad Atif; Muhammad Imran; Musinguzi Alex; Jawairia Fatima; null Dilawaiz; Maria Abrar; Hafiz Zeshan Haider (Journal of Chemistry)
Epoxy composites as per their excellent adhesive behavior, mechanical strength, electrical insulation, and chemical resistance have been utilized in a number of applications and constitute a major chunk of polymer industry. Epoxy, since ages, has been derived from petrochemicals which has been a major source of environmental pollution and has drawn a limit at various applications. This datum highlights the dire need of bio-based materials, for their nontoxic, eco-friendly, economical, and renewable behavior. To counter the pollution factor associated with petrochemical-derived epoxies, various epoxidation strategies on bio-based materials have been reported with designed reagents (catalyst, acid, enzyme, or metal). This review has been compiled for latest progressions in epoxidation approaches of bio-based materials, considering them as potentially eco-friendly green replacements of petrochemical resources. It has a lot of information of usage of bio-waste and their property. The thermal and photocuring discussed with the different techniques. In thermal technique hardening agent which gave epoxy the definite structure and in photocuring PI agent used for curing and making them polymer but they showed crucial effect on environment. After that other bio-based epoxidation (BBEP) strategical techniques introduced such as hypochlorination (most primitive technique at small scale and gave 93% selectivity with minimum by-products), homogeneous and heterogeneous catalysis, chemoenzymatic method, and metal catalyzed reactions have been compared in this review based on chemistry involved in epoxidation reaction. This article summarizes a large number of precursors, reagents, and reaction conditions for a wide variety of end products and applications, allowing the reader to see experimental alternatives and their potential benefits in a single place.